2017
DOI: 10.1190/geo2015-0595.1
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Hessian-free Gauss-Newton full-waveform inversion via l-BFGS preconditioned conjugate-gradient algorithm

Abstract: Full-waveform inversion (FWI) has emerged as a powerful strategy for estimating subsurface model parameters by iteratively minimizing the difference between synthetic data and observed data. The Hessian-free (HF) optimization method represents an attractive alternative to Newton-type and gradient-based optimization methods. At each iteration, the HF approach obtains the search direction by approximately solving the Newton linear system using a matrix-free conjugate-gradient (CG) algorithm. The main drawback wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 71 publications
0
30
0
Order By: Relevance
“…However, this inversion requires a significant number of iterations. In our case, around 800 iterations were performed, which can probably be reduced by modifying the optimization engine (for example, by using alternative optimization algorithms) [ Pan et al ., ]. After the baseline model is recovered, each monitor survey can be inverted from the maximum available frequency, and it takes fewer iterations to converge (80 in our case).…”
Section: Discussionmentioning
confidence: 99%
“…However, this inversion requires a significant number of iterations. In our case, around 800 iterations were performed, which can probably be reduced by modifying the optimization engine (for example, by using alternative optimization algorithms) [ Pan et al ., ]. After the baseline model is recovered, each monitor survey can be inverted from the maximum available frequency, and it takes fewer iterations to converge (80 in our case).…”
Section: Discussionmentioning
confidence: 99%
“…This method includes a nested loop in numerical implementation: an outer loop for solving a nonlinear problem to update model parameters and an inner loop for solving a linear problem to reduce Hessian effects and optimize gradients. When a large iteration number is used in the inner loop, this approach is still expensive in real applications (Pan et al, 2017). Another popular Hessian‐free method is the L‐BFGS algorithm (Byrd et al, 1994; Nocedal, 1980; Nocedal & Wright, 2006), which has a good trade‐off between computational efficiency and accuracy for large‐scale inverse problems.…”
Section: Methodsmentioning
confidence: 99%
“…(3.12) in this paper and Eq. ( 13) in [76]). Similar to the GN Hessian (equation 10 in [76]), the element of the Hessian in our approach is formed by correlating the two Frechet derivative wavefields at the receivers, which is a approximate Hessian.…”
Section: Some Details For Implementationmentioning
confidence: 98%
“…( 13) in [76]). Similar to the GN Hessian (equation 10 in [76]), the element of the Hessian in our approach is formed by correlating the two Frechet derivative wavefields at the receivers, which is a approximate Hessian. Actually, it has been demonstrated that the Distorted Born iterative method is consistent with the Gauss-Newton methods of optimization (see Remis and van den Berg [74], Oristaglio and Blok [73], Jakobsen and Ursin [24].…”
Section: Some Details For Implementationmentioning
confidence: 99%